Global Currents of Public Management Reform: OECD Trends and Their Adaptation in Indonesian Governance - Arif Setia Budi; Chandra Dinata; I Made Arie Widyasthana Wartana Putra; Renia F. De La Peña (University of Merdeka Malang, 2026)
Public management reform has developed as a global trend since the 1980s, in line with the increasing complexity of public issues and demands for more effective and accountable governance. Member countries of the Organisation for Economic Co-operation and Development (OECD) play a crucial role in shaping and disseminating the public management reform paradigm through the development of modern governance standards and practices. This article aims to analyze the development of contemporary public management theory and examine how OECD reform trends are adapted to the context of Indonesian governance. This research uses a qualitative approach with a systematic literature review design. The literature search was conducted through Scopus-indexed international journals from 2021–2025 using the keywords public management and OECD. Selected articles were analyzed thematically to identify patterns of theory development, the role of the OECD as a global normative actor, and the dynamics of reform adaptation at the national level. The study results indicate that public management reform within the OECD has shifted from the New Public Management approach to a post-New Public Management framework that emphasizes cross-institutional coordination, institutional capacity, and policy integration. In the Indonesian context, these principles have been selectively adopted through bureaucratic reform, performance-based management, regulatory reform, and digital government. However, their implementation faces structural challenges, resulting in a hybrid governance pattern. These findings confirm that OECD-based reforms require contextual adjustments to sustainably strengthen the quality of public governance.